Cash is not king in incentivizing online surveys. Issue 2 (19th January 2021) - Knowles, Stephen; Stahlmann-Brown, Philip
ABSTRACT: We analyse the effect of different incentive structures on response rates for an online survey of New Zealand landowners who have previously not responded to an earlier wave of the survey. We find response rates are lowest for direct cash payment, lower even than for a control group with no incentive, which may be due to direct payment extinguishing any warm glow people receive from the charitable act of completing a survey. Lottery and charitable donation incentives do not increase response rates relative to a control group with no incentive.